The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/f12050571
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Three Circular Mitochondrial Genomes of Fagus sylvatica from Germany and Poland Reveals Low Variation and Complete Identity of the Gene Space

Abstract: Similar to chloroplast loci, mitochondrial markers are frequently used for genotyping, phylogenetic studies, and population genetics, as they are easily amplified due to their multiple copies per cell. In a recent study, it was revealed that the chloroplast offers little variation for this purpose in central European populations of beech. Thus, it was the aim of this study to elucidate, if mitochondrial sequences might offer an alternative, or whether they are similarly conserved in central Europe. For this pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…As it has previously been shown that organelle DNA insertions can be uneven across the genome and associated with chromatin structure ( Wang and Timmis 2013 ), their distribution in the genome of Bhaga was analysed. For both chloroplast ( Mishra et al, 2021a ) and mitochondria ( Mishra et al, 2021b ), multiple integrations of fragments of variable length were observed in all chromosomes (Figures 3 , 4 ). These fragments varied in length from the minimum size threshold (100 bp) to 54,784 bp for the chloroplast and to 26,510 bp for the mitochondrial DNA.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…As it has previously been shown that organelle DNA insertions can be uneven across the genome and associated with chromatin structure ( Wang and Timmis 2013 ), their distribution in the genome of Bhaga was analysed. For both chloroplast ( Mishra et al, 2021a ) and mitochondria ( Mishra et al, 2021b ), multiple integrations of fragments of variable length were observed in all chromosomes (Figures 3 , 4 ). These fragments varied in length from the minimum size threshold (100 bp) to 54,784 bp for the chloroplast and to 26,510 bp for the mitochondrial DNA.…”
Section: Resultsmentioning
confidence: 96%
“…Separately assembled chloroplast ( Mishra et al, 2021a ) and mitochondrial ( Mishra et al, 2021b ) genomes were aligned to the genomic assembly using blastn with an e-value cut-off of 10e-10 and 100 bp word size. Information for different match lengths and different identity cut-offs were tabulated and analysed.…”
Section: Methodsmentioning
confidence: 99%
“…An important solution to the problem of different marker systems, as well as the need to select a priori to study either neutral or functional genetic diversity, is on the horizon in the form of cost-effective whole-genome sequencing and sequence analysis to identify single-nucleotide polymorphisms (SNPs) and other genomic markers. Reference nuclear (Mishra et al 2022), plastid (Mader et al 2019;Mishra et al 2021b), and mitochondrial (Mishra et al 2021a) genomes of F. sylvatica have recently been published. Yet, the currently employed methods for cost-effective SNP identification, such as restriction-site-associated DNA (RAD) sequencing (Peterson et al 2012), tend to bias results toward neutral loci and have high missing data rates.…”
Section: Introductionmentioning
confidence: 99%